Manfaat Laba dan Arus Kas Untuk Memprediksi Kondisi Financial Distress pada Perusahaan Textile Mill Products dan Apparel and Other Textile Products yang Terdaftar di Bursa Efek Jakarta - Atmini, Sari; Andayani, Wuryan (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2006)
Financial distress condition happens before bankruptcy. This condition can be predicted using models that have developed by many researchers. Most financial distress prediction models rely on financial data, which is easier to obtain, and focus on earnings. The purpose of this research is to examine whether cash flow or earnings that can better predict financial distress condition of a firm. Besides, this research tries to build a model to predict financial distress condition of a firm using financial and non-financial data. This research uses analysis sample and holdout sample. The analysis sample consists of 60 firm-year from 24 different firms in earnings model and 60 firm- year from 24 different firms in cash flow model. The holdout sample consists of 23 firms. The statistic method used is multiple discriminant analysis (MDA). The result of this study shows that earnings can better predict financial distress condition. In other words, it is harder to predict financial distress condition defined in terms of cash flow than in profitability. Key words: financial distress, cash flow, earnings